2014
DOI: 10.5194/se-5-131-2014
|View full text |Cite
|
Sign up to set email alerts
|

Thermal shock and splash effects on burned gypseous soils from the Ebro Basin (NE Spain)

Abstract: Abstract.Fire is a natural factor of landscape evolution in Mediterranean ecosystems. The middle Ebro Valley has extreme aridity, which results in a low plant cover and high soil erodibility, especially on gypseous substrates. The aim of this research is to analyze the effects of moderate heating on physical and chemical soil properties, mineralogical composition and susceptibility to splash erosion. Topsoil samples (15 cm depth) were taken in the Remolinos mountain slopes (Ebro Valley, NE Spain) from two soil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Overall, the recuperation was fast, and the conjugation of several conditions such as flowering season, rainfall and nutrient availability, facilitated the plant germination. Severe wildfires lead to high rates of erosion and nutrient losses (Thomas et al, 2000;Novara et al, 2010;Varela et al, 2010;Leon et al, 2014), reducing the capacity of soils (Martin et al, 2012;Guenon et al, 2013;Aznar et al, 2015;Hedo et al, 2015) and ecosystems to recuperate (Úbeda et al, 2006). These fires are the ones that cause serious soil and land degradation (Fernandez et al, 2007).…”
Section: Overall Discussion and Implications For Land Managementmentioning
confidence: 99%
“…Overall, the recuperation was fast, and the conjugation of several conditions such as flowering season, rainfall and nutrient availability, facilitated the plant germination. Severe wildfires lead to high rates of erosion and nutrient losses (Thomas et al, 2000;Novara et al, 2010;Varela et al, 2010;Leon et al, 2014), reducing the capacity of soils (Martin et al, 2012;Guenon et al, 2013;Aznar et al, 2015;Hedo et al, 2015) and ecosystems to recuperate (Úbeda et al, 2006). These fires are the ones that cause serious soil and land degradation (Fernandez et al, 2007).…”
Section: Overall Discussion and Implications For Land Managementmentioning
confidence: 99%
“…However, black carbon decomposition is controversial, and there are different views on this issue. Some studies argue that black carbon decomposes very slowly (Liu et al, 2008) or is practically non-degradable (González-Pérez et al, 2004), while others show that it is successfully affected by chemical (Cheng et al, 2006(Cheng et al, , 2008 and microbial (Knicker et al, 2013;Marschner et al, 2008) oxidation. The assumption of black carbon complete stability in soils is doubtful because its content varies considerably in different soils.…”
Section: Soil Profile Analysis and Physico-chemical Propertiesmentioning
confidence: 99%
“…Many Mediterranean soils are considered to be sensitive to recurrent wildfires with progressive degradation processes that affect their level of fertility (Pascual et al ., ) and microbial activities (Guénon et al ., 2011, 2013). Numerous soil studies reported that wildfires reduced the soil organic matter, the aggregate stability, increase the surface wash and the erosion rates and finally induce the soil degradation (González‐Pelayo et al ., ; Novara et al ., ; Bodí et al ., ; Carreiras et al ., ; León et al ., ). Increase in fire frequency can reach a critical point leading to a shift in properties of Mediterranean ecosystems (Guénon et al ., ) that might be difficult to reverse without a significant improvement of soil quality.…”
Section: Introductionmentioning
confidence: 99%